To the moon a push and pull adventure - Black, Allison (London ladybird books, 2019)
Summary:Blast off into space in this interactive adventure based on the Apollo Moon landings. Curious minds will love to explore the rocky surface of the Moon with this interactive title from the Little World series. Follow in the footsteps of the first lunar astronauts in this bright and colorful board book, which features a sturdy novelty to slide, push or pull on every spread . . . including double pulls that go up, up and up!
English stories
Keywords: English stories; Astronauts Juvenile fiction; Toy and movable books